Recommendations on phenylketonuria in Turkey - Coşkun, Turgay; Çoker, Mahmut; Mungan, Neslihan Önenli; Özel, Hülya Gökmen; Sivri, H Serap (The Turkish Journal of Pediatrics, 2022)
Background. Phenylketonuria (PKU), is an autosomal recessive disease leading to the conversion defect of phenylalanine (Phe) into tyrosine. Severe neurocognitive and behavioral outcomes are observed in untreated cases. The present paper aims to review clinical experiences and expert recommendations in diagnosis, treatment, and follow-up of pediatric PKU patients in Turkey. Methods. Two advisory board meetings were held in the year 2016 and 2017 with contributions of four leading experts in this field, and an online update meeting was held for final decisions about statements, and conclusions in January 2021. Considering management gaps in diagnosis, treatment, and follow-up of PKU, discussion points are defined. The Committee members then reviewed the Turkish and general literature and the final statements were formulated. Results. The diagnostic cut-off for dried blood spots should remain at 2 mg/dl. Treatment cut-off value is acceptable at 6 mg/dl. Compliance with an ideal follow-up list is strongly recommended. Total protein intake should not be limited. Age-related safe levels of protein intake should be encouraged with an additional 40% from L-amino acids supplements, a 20% compensatory factor to account for the digestibility and utilization of amino acids from the supplement, and a further 20% compensation to optimize Phe control. Cognitive impairment and intelligence quotient evaluations should be performed at least twice before 3 years of age. In pregnant women, the target Phe level should be < 5 mg/dl, and they should be followed-up weekly in the first trimester, then every 2 weeks after organogenesis. Novel pharmacological treatments are promising, but some of them have limitations for our country. Conclusions. Early diagnosis and treatment initiation; determination and standardization of diagnostic and treatment thresholds; treatment modalities and follow-up parameters are significant steps in treating PKU in the long term. PKU follow-up is a dynamic process with uncertainties and differences in clinical practice.